The network of mental health care from the family health strategy service - Christine Wetzel; Leandro Barbosa de Pinho; Agnes Olschowsky; Ariane da Cruz Guedes; Marcio Wagner Camatta; Jacó Fernando Schneider
The Family Health Strategy Service (FHSS) is an important ally in the mental health system, contributing to the completeness and effectiveness of care. This study aimed to discuss the mental health care network as compared to the daily routine of an FHSS. It is an evaluative study with a qualitative methodological approach. It was developed in an FHSS in Porto Alegre-RS, Brazil. Data was collected between July and December of 2010 through interviews with 16 workers and ten relatives. We identified important resources in primary health care, such as partnerships with academia. However, the constitution of this care is still based on specialty, following the logic of patient referral. Our intention for this study was to contribute to the operationalization of the mental health care network, consolidating the partnership with the FHSS and developing activities in the territorial space, raising awareness, demystifying health care service in the area, and countering the perception that it is uniquely specialized.